2016
DOI: 10.1177/1462474516673822
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation nation: American penal policy in late mass incarceration

Abstract: The question has been posed whether current developments in American penal policy toward reducing prison populations and sentences for low level, nonviolent offenses might reflect the end of the mass incarceration era. Yet articulation of precisely what defines the present in American penal policy remains unclear. This paper identifies three distinctive features: a national-level program of comprehensive criminal justice reevaluation and reform in response to the excesses of recent policy; the distinguishing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 28 publications
3
82
0
Order By: Relevance
“…This hypothesis is consistent with the argument that penal change rarely represents a sudden rejection and replacement of past practices and policies (Goodman et al 2014, Campbell & Schoenfeld 2013. It is also bolstered by evidence that states have continued to expand life-without-parole (LWOP) statutes even as they enacted decarcerative reforms pertaining to drug and other nonviolent offenses (Seeds 2016).…”
Section: Bifurcation: Is the Low-hanging Fruit Enough?supporting
confidence: 71%
See 4 more Smart Citations
“…This hypothesis is consistent with the argument that penal change rarely represents a sudden rejection and replacement of past practices and policies (Goodman et al 2014, Campbell & Schoenfeld 2013. It is also bolstered by evidence that states have continued to expand life-without-parole (LWOP) statutes even as they enacted decarcerative reforms pertaining to drug and other nonviolent offenses (Seeds 2016).…”
Section: Bifurcation: Is the Low-hanging Fruit Enough?supporting
confidence: 71%
“…In their analysis of media rhetoric and legislative reforms enacted from 2000 through 2012, Beckett et al (2016) found that reforms pertaining to nonviolent offenses were often legitimated in terms of the need to ensure that sufficient resources are available to incarcerate people convicted of violent crimes for even longer periods of time. It thus appears quite possible that late mass incarceration (Seeds 2016) will be characterized by shorter sentences or diversion for a handful of less-serious crimes such as drug possession and theft but even longer sentences for violent and sex offenses (and possibly drug dealing). Given that sentences imposed in the United States for all types of crime are already substantially longer than those imposed in comparable countries (Tonry 2016) and that one in seven prisoners is currently serving a life sentence (Nellis 2017), this possibility is quite sobering.…”
Section: Bifurcation: Is the Low-hanging Fruit Enough?mentioning
confidence: 99%
See 3 more Smart Citations